Desempenho funcional global e assistência do cuidador no autismo infantil e síndrome de Asperger - Guimarães Pozzato, Michele Gea [UNIFESP] (2010)
Introduction: Childhood autism and Asperger’s syndrome belong to a family of neurodevelopmental disorders called Pervasive Development Disorders. This group is characterized by qualitative abnormalities in reciprocal social interactions and modes of communication as well as a restricted repertoire of stereotyped, repetitive interests and activities. While it is recognized that such patients exhibit impairment in at least three of the aforementioned areas, studies assessing overall functional performance have not been carried out for the identification and comprehension of the peculiarities of each condition. Objectives: The aims of the present study were to 1) quantify the overall functional performance and need for caregiver assistance in childhood autism (CA) and Asperger’s syndrome (AS), 2) compare the findings between groups and to normative data from Brazilian children and 3) determine whether the PEDI test can be used as an auxiliary method for the diagnosis of CA and AS. Methods: A cross-sectional study was carried out involving 52 children between three and eight years of age diagnosed with either CA (n=26) or SA (n=26). The Brazilian version of the Pediatric Evaluation of Disability Inventory (PEDI) was administered in the form of a structured interview with the caregiver and direct observation. Results: The children with CA and AS achieved significantly lower scores than that expected for normality. The children with AS had a significantly better social function than those with CA. However, those with CA achieved significantly better scores than those with AS on activities related to self-care and mobility, requiring less assistance. Conclusion: Children with CA and AS exhibit deficits in all aspects of development in comparison to normal children. While patients with AS are better at social interaction than typical autistic children, they exhibit greater deficits with regard to basic tasks, such as self-care and mobility, requiring greater assistance than children with CA. The particularities observed may assist in the determination of the diagnosis and suggest a differentiated approach in the rehabilitation process.